Pengaruh Penambahan Tepung Tulang Ikan Lele (Clarias Batrachus) pada Pembuatan Mie Basah Terhadap Kadar Kalsium, Elastisitas, dan Daya Terima - Permitasari, Witdiah; , Rusdin Rauf, S.TP., M.P; , Fitriana Mustikaningrum, S.Gz, M.Sc (2013)
Background: Calcium is one of the micronutrients that has an important role in human health, because deficiency of calcium can lead osteoporosis. The strategy to increase the calcium intake is the addition of bone flour in wet noodle-making Purpose : The purpose of the study was to evaluate the effect of catfish bone flour addition on calcium content, elasticity and acceptability of wet noodle. Methods: The completely randomized design was used in the research with 4 treatments of calcium addition, were 0%, 10%, 20% and 30%. Data were analyzed using One Way Anova, followed by DMRT test at a level 0,05. Results: The results indicated that there was an effect of catfish bone flour addition on calcium level of wet noodles. The addition 30% displayed the highest calcium content of wet noodle, which was 5,14%. However, the elasticity and acceptability of wet noodles were not affected by the addition of catfish bone flour. Suggestion: In the manufacture of wet noodles, suggested to use 10% of catfish bone flour.